2009
DOI: 10.1038/emboj.2009.19
|View full text |Cite
|
Sign up to set email alerts
|

Snapshots of the RNA editing machine in trypanosomes captured at different assembly stages in vivo

Abstract: Mitochondrial pre-messenger RNAs in kinetoplastid protozoa are substrates of uridylate-specific RNA editing. RNA editing converts non-functional pre-mRNAs into translatable molecules and can generate protein diversity by alternative editing. Although several editing complexes have been described, their structure and relationship is unknown. Here, we report the isolation of functionally active RNA editing complexes by a multistep purification procedure. We show that the endogenous isolates contain two subpopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 56 publications
7
89
1
Order By: Relevance
“…It remains to be investigated how the architecture of the core of the editosome described in this work can be integrated with the recently reported three-dimensional structures of 20S editosomes (55,56). Golas et al (56), using complexes purified via tagged KREPA3, reported a bipartite appearance in the majority of their structures, which might reflect the division into FIGURE 9.…”
Section: Discussionmentioning
confidence: 73%
“…It remains to be investigated how the architecture of the core of the editosome described in this work can be integrated with the recently reported three-dimensional structures of 20S editosomes (55,56). Golas et al (56), using complexes purified via tagged KREPA3, reported a bipartite appearance in the majority of their structures, which might reflect the division into FIGURE 9.…”
Section: Discussionmentioning
confidence: 73%
“…Our CXMS data creates a detailed framework for the global architecture of editosome complexes, and can therefore provide context to reinterpret existing low-resolution electron microscopy data. For example, electron microscopy images of TAP-purified editosomes from T. brucei and Leishmania tarentolae revealed bipartite particles composed of two approximately equally sized, but structurally different globular domains that are connected via an interface (70,71). These studies also indicated that most editosome proteins are likely present as single copies in the complex, although the exact stoichiometry of editosomes remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…During the revision of our paper, a paper by Golas et al was published describing 3D structures of the editing complexes of T. brucei (23). Approximate location of REL1 on unbiased single-particle reconstruction.…”
Section: Methodsmentioning
confidence: 99%